Cost analysis in the implementation of ISO quality system in a petroleum refinery (2009)
The substantial amounts of financial and non-financial resources invested annually on petroleum refinery operations justify the need for documentation on the cost of implementing ISO quality systems ill refineries. The experience of ISO quality system implementation cost analysis in a petroleum refinery in a developing country is reported with a combination of mathematical model and application. The concept of strain as a function of growth in the physical sciences is adopted to conceptualise the growth phenomenon in the ISO organisation. Practically, developing a quantitative approach in evaluating cost of ISO implementation would help the manager in relying on scientific fact instead or intuition. The approach is new and has the potential for helping the top management in planning the strategy and allocating necessary funds for effective implementation of ISO quality systems.